A method for assessing kinematic bending moments at the pile head. - De Sanctis, Luca (Earthquake engineering & structural dynamics.)
The conventional design methods for seismically loaded piles still concentrate in providing adequate resistance from the pile to withstand only the inertial bending moments generated from the oscillation of the superstructure, thus neglecting the effect of kinematic interaction between pile and soil. By contrast there has been extensive research on kinematic effects induced by earthquakes and a number of simplified methods are available for a preliminary evaluation of kinematic bending moments at the interface between two soil layers. Less attention has been paid to the effects of kinematic interaction at the pile-head. The paper summarizes recent research work on kinematic response analysis of fixed-head piles aimed at the performance evaluation of a piled foundation. Results from an extensive parametric study, undertaken by means of three-dimensional FE analyses, suggest a new criterion to predict kinematic bending effects at the pile head, where the combination of kinematic and inertial effect may be critical.